DESAIN DIDAKTIS MATERI PENGUKURAN PANJANG MENGGUNAKAN SITUATION-BASED LEARNING UNTUK MENGATASI HAMBATAN BELAJAR ACCAPTANCE FINDING SISWA SEKOLAH DASAR - Rosdiyana, Rosdiyana; Isrok'atun, Isrok'atun; Iswara, Prana Dwija (Jurnal Pena Ilmiah, 2019)
Measurement is one of the important mathematical concepts. Studying material about â€œpengukuran panjangâ€ is not easily understood by students. This is evident from the number of learning obstacles experienced by students in learning. One of the obstacles experienced about â€œpengukuran panjangâ€ can occur because students have low accaptance finding skills. Such problems encourage researchers to minimize learning obstacle students. These efforts are carried out by implementing a didactic design characteristic SBL to overcome learning obstacles in accaptance finding skills regarding â€œpengukuran panjangâ€ students grade IV. The research method used is DDR. The research began with preliminary study. Furthermore, the didactic design hypothesis to be implemented. The result of the implementation students indicate tendency to a particular response, so that it can produced a revised didactic design implemented for better teaching materials result. Data collection techniques used are through test instrument in of question, participatory observation, interviews, documentation and the combination of all there or triangulation.